WATERSTORY ILE: A Systemic Approach to Solve a Long-Lasting and Far-Reaching Problem. (June 2015) - Bassi, Andrea M.; De Rego, Frank; Harrisson, John; Lombardi, Niccolò
Background: Sustainable management of the municipal water supply is a priority issue in the policy agenda of Maui County, Hawaii. The Maui Economic Development Board launched the WaterStory initiative to educate residents about the determinants and history of Maui's water resource development. A System Dynamics model was developed and coupled with a user interface to create WATERSTORY, an interactive learning environment (ILE). Purpose: The purpose of this study was to analyze the benefits of WATERSTORY for the identification and assessment of sustainable water management policies in Maui. Method: WATERSTORY is a System Dynamics-based ILE that shows the cross-sectoral impacts of users' decisions. Both, the simulation model and the ILE resulted from group modeling and ILE testing sessions. Results: The development of the WATERSTORY ILE facilitated the involvement of local communities in the discussion of water management problems and identification of possible solutions. Conclusions: The study suggests that developing a simple ILE is essential in raising the interest of a wide audience involved in sustainable development policy making. After stakeholders gain confidence in the benefit of the ILE, it becomes easier to integrate simulation exercises into planning processes at national, regional and local levels.